2021
DOI: 10.23970/ahrqepccer243
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Airway Management: A Systematic Review

Abstract: Objective. To assess the comparative benefits and harms across three airway management approaches (bag valve mask [BVM], supraglottic airway [SGA], and endotracheal intubation [ETI]) by emergency medical services in the prehospital setting, and how the benefits and harms differ based on patient characteristics, techniques, and devices. Data sources. We searched electronic citation databases (Ovid® MEDLINE®, CINAHL®, the Cochrane Central Register of Controlled Trials, the Cochrane Database of Systematic Review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…A systemic review evaluated the benefits and harms of three airway management approaches (bag valve mask, supraglottic airway, and endotracheal intubation) used in prehospital settings on patients with TOHCA [ 13 ]. The review did not demonstrate that more invasive airway approaches improve survival and ROSC rates.…”
Section: Discussionmentioning
confidence: 99%
“…A systemic review evaluated the benefits and harms of three airway management approaches (bag valve mask, supraglottic airway, and endotracheal intubation) used in prehospital settings on patients with TOHCA [ 13 ]. The review did not demonstrate that more invasive airway approaches improve survival and ROSC rates.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have reported mixed results regarding the application of AAM compared with bag-valvemask (BVM) ventilation. [1][2][3][4][5][6][7][8] It might be explained by the nonnegligible risk of failed AAM application, longer procedural time, lack of expertise required for AAM, [9][10][11] the need of interrupt chest compression, 12,13 or complications such as aspiration or regurgitation. 14 Study of a large-scale real-world data might clarify the clinical efficacy of prehospital AAM.…”
Section: Introductionmentioning
confidence: 99%
“…In the prehospital stage of out‐of‐hospital cardiac arrest (OHCA), securing oxygen supply and providing effective ventilation with the application of advanced airway managements (AAM) seems a reasonable and logical action. However, studies have reported mixed results regarding the application of AAM compared with bag–valve–mask (BVM) ventilation 1–8 . It might be explained by the nonnegligible risk of failed AAM application, longer procedural time, lack of expertise required for AAM, 9–11 the need of interrupt chest compression, 12,13 or complications such as aspiration or regurgitation 14 …”
Section: Introductionmentioning
confidence: 99%
“…In some conditions, DL could be challenging from both anatomic and physiologic difficulties, which leads to a higher chance of failed intubation and worsening outcome. 7 , 8…”
Section: Introductionmentioning
confidence: 99%